Tails from the Exotic Feline Rescue Center, 25th Anniversary Edition - Stephen D. McCloud; Joe Taft (Indiana University Press, 2016)
Meet Sahib, Sampson, Zulu, Rouge, Blaze-just a few of the 200 big cats that await visitors at the Exotic Feline Rescue Center. The EFRC, in Center Point, Indiana, is a nationally recognized leader in big cat rescue, conservation, and care. Almost all of these cats-tigers, bobcats, lions, pumas, and servals-are survivors of abuse and neglect. In this follow-up to Saving the Big Cats and Real Stories of Big Cat Rescues, photographer Stephen D. McCloud showcases the newest residents of this lush 108-acre sanctuary, now celebrating its 25th anniversary. Readers will be fascinated by the stories of these incredible feline predators in this anniversary edition, which includes a foreword by Tigers of America founder Bill Nimmo.